Improved fisheries productivity and management in tropical reservoirs - Béné, Christophe; Abban, E.K.; Abdel-Rahman, S.H.; Ayyappan, S.; Brummett, R.E.; Dankwa, H.R.; Das, Anup K.; Habib, O.A.; Katiha, P.K.; Kolding, J.; Obirih-Opareh, N.; Ofori, J.K.; et al. (CGIAR Challenge Program on Water and Food, 2009)
“Improved fisheries productivity and management in tropical reservoirs” The objective of the project was to contribute to the current research on reservoirs enhancement fisheries in tropical countries through the implementation of a series of action-research activities implemented in two small reservoirs in the Indo-Gangetic basin in India, and two very large reservoirs in Africa, the Lake Nasser (Egypt), and the Volta Lake (Ghana). Socio-institutional analyses were also conducted in these reservoirs to improve our knowledge regarding some of the main social processes that influence reservoir productivity. Overall the results of the project stress that while the natural biophysical constraints of the reservoirs are important in defining the ecological production processes, it is the socio-economic settings characterizing the community/societies around the reservoirs that eventually shape the human production enhancement possibilities.